2006
DOI: 10.1534/genetics.105.051557
|View full text |Cite
|
Sign up to set email alerts
|

The mushroom body defect Gene Product Is an Essential Component of the Meiosis II Spindle Apparatus in Drosophila Oocytes

Abstract: In addition to their well-known effects on the development of the mushroom body, mud mutants are also female sterile. Here we show that, although the early steps of ovary development are grossly normal, a defect becomes apparent in meiosis II when the two component spindles fail to cohere and align properly. The products of meiosis are consequently mispositioned within the egg and, with or without fertilization, soon undergo asynchronous and spatially disorganized replication. In wild-type eggs, Mud is found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 39 publications
4
48
0
Order By: Relevance
“…We focused on Mud (Mushroom body defect), the Drosophila homologue of NuMA, for several reasons: vertebrate NuMA is known to interact directly with Dynein to assemble the mitotic spindle, and its Drosophila and C. elegans homologues interact with Dynein to position the spindle in neuroblasts and the one-cell stage embryo [52][53][54][55][56] ; mud null alleles are viable but females are sterile and males are fertile, indicating a specific requirement for mud in female germ cell development; Mud is an essential component of the meiosis II spindle in Drosophila oocyte 57 ; and Mud is expressed in the germarium and localizes to the nuclear envelope 57 (Figs 7a and 8f).…”
Section: The Dynein-interacting Protein Mud Co-localizes With Klarsicmentioning
confidence: 99%
“…We focused on Mud (Mushroom body defect), the Drosophila homologue of NuMA, for several reasons: vertebrate NuMA is known to interact directly with Dynein to assemble the mitotic spindle, and its Drosophila and C. elegans homologues interact with Dynein to position the spindle in neuroblasts and the one-cell stage embryo [52][53][54][55][56] ; mud null alleles are viable but females are sterile and males are fertile, indicating a specific requirement for mud in female germ cell development; Mud is an essential component of the meiosis II spindle in Drosophila oocyte 57 ; and Mud is expressed in the germarium and localizes to the nuclear envelope 57 (Figs 7a and 8f).…”
Section: The Dynein-interacting Protein Mud Co-localizes With Klarsicmentioning
confidence: 99%
“…Pins requirement has not been reported in the oocyte. However, Mud is distributed around the nucleus (Yu et al, 2006), like the Dynein-Dynactin complex with which it has been reported to control spindle attachment in other systems (Gonczy, 2008). However, although the positioning of the nucleus is Dynein dependent (Januschke et al, 2002), it does not necessarily require Mud (Yu et al, 2006).…”
Section: /Sktlmentioning
confidence: 99%
“…The Mushroom body defect (Mud) protein shows limited sequence similarity to NuMa and was shown to bind Pins, the fly homolog of the NuMa binding partner Lgn (Bowman et al, 2006;Izumi et al, 2006;Siller et al, 2006). Mud is required for correct spindle orientation in neuroblasts (Bowman et al, 2006;Izumi et al, 2006;Siller et al, 2006) and for meiosis II in female flies (Yu et al, 2006), but a function in spindle pole organization has not been demonstrated so far. The protein encoded by abnormal spindle (asp) localizes to microtubule minus ends at metaphase spindle poles and is required for focussing of spindle poles (Saunders et al, 1997; do Carmo Avides and Glover,…”
Section: Introductionmentioning
confidence: 99%